1156 Voc's in container, study of health problems in 125 french dockers. (24th April 2018) - Lucas, D; Despres, I; Jegaden, D; loddé, B
Abstract : Introduction: The EOM society published four years ago, a specific questionnaire, FUMEX questionnaire, on health impact of fumigants and other VOC's in containers. The aims of this study were to evaluate exposure and health impact in dockers. Methods: Dockers are interviewed in face to face by a nurse or an occupational physician from Port occupational health centre of Le Havre and Brest from april to September 2015. Questionnaires were analysed by sphinx software. Results: 125 questionnaires were included and analysed. Mean age was 35 years, 46% were smokers. More than 80% declared not being exposed to fumigants or VOC's. Exposures were mostly described for refrigeration technicians (21%), or during port engine driving, handling containers. Symptoms most frequently described were headaches (42%), fatigue (50%), sleeping disorders (33, 6%), and pulmonary irritation (31%). Only 22.4% wore regularly protective equipment. Phosphine is the fumigant mostly mentioned. Discussion: Most exposed of port workers seem to be now refrigeration technicians and logistic workers. A lack of knowledge on risk and prevention's measures is evident and important. The FUMEX questionnaire is too complicated to be relevant for daily prevention in occupational health services. It's more needed for physicians or in hospital or researchers working with suspicious cases. A shorter and more comprehensible questionnaire was created.